Estimating glomerular filtration rate in obese subjects. Issue 2 (March 2015) - Nguyen, Minh T.; Fong, Julia; Ullah, Shahid; Lovell, Alex; Thompson, Campbell H.
Summary The glomerular filtration rate (GFR) can be estimated by an equation that incorporates patients' age, gender, creatinine and weight or, ideally, lean body mass (LBM). However, measuring LBM is not easy if the patient is obese. The aim was to determine an acceptable bedside method for GFR estimation in obese patients. In 82 obese Caucasian outpatients, anthropometric and other characteristics were collected including LBM by impedance analysis. Estimates of GFR were compared with a reference equation (CCGLBM) using Bland–Altman plots, correlation analysis and an independent sample t-test. The patients (72% female) were aged 43.1 ± 12.7 years with BMI 47.0 ± 8.0 kg/m2, height 168.4 ± 9.4 cm and serum creatinine 70.3 ± 25.7 μM. The GFR estimated by the CCGLBM equation was 98.2 ± 33.6 ml/min compared to other equations which ranged from 100.0 ± 22.8 to 218.4 ± 85.5 ml/min. Any equation incorporating actual body weight overestimated the GFR by >120 ml/min (p < 0.001) with a significant fixed proportional bias (p < 0.001). For GFRs between 20 and 180 ml/min, an equation using ideal body weight (CCGIBW) equated to the CCGLBM estimate. The Modified Diet in Renal Disease and Chronic Kidney Disease Epidemiology Collaboration equations performed as well as the CCGLBM in estimating GFR but with proportional bias (p < 0.001). Considering the ease of calculation of the CCGIBW at the bedside, it has a role in GFR estimation of obese inpatients.